Analisis Sistem Pembayaran Digital Pada Era Globalisasi - William Angelo Tio; Johny Budiman (Universitas Internasional Batam, 2021)
This study aims to determine: (1) Solutions so that the digital payment system can be applied in the wider community (2) Positive survey results to be used as an example in advancing the economic industry (3) What factors can encourage people's intention to use a digital payment system. The form of this research is descriptive qualitative, the source of which is taken from research data that has previously existed on the internet. The research method used in this research is a questionnaire method in which the researcher distributes data containing questions to get answers and information needed by the researcher. Based on the research results, it can be concluded that: (1) Customer satisfaction is one of the impacts for the intention to reuse digital payment systems (2) Trust is also an important element in increasing customer interest in digital payment systems.